Pemanfaatan Internet sebagai Media Komunikasi oleh Pengelola Sekretariat Dewan Ketahanan Pangan Provinsi - Munawar Khalil; Amiruddin Saleh; Basita Ginting (Institut Pertanian Bogor, 2017)
This research work was carried out to analyze the utilization of internet as a communication media by Staff of Provincial DKP Secretariat. The population of the study is Staff of Provincial DKP Secretariat in 34 province in Indonesia. Survey method of the research and stratified random sampling were used to select 68 Staff for the study. The data was presented and analyzed in tables and average scores. The research found that internet exposure of Staff of Provincial DKP Secretariat is high. However, its utilization is still low. The research also showed that: (1) individual characteristics (age, period of work, and training) are significantly correlated with internet exposure (frequency and channel variety); (2) motivation (intrinsic motivation) is significantly correlated with internet exposure (duration and the situation of exposure); (3) internet exposure (duration, frequency, and the situation of exposure) are significantly correlated with utilization of internet (communication and coordination).